Formal grammar 14th International Conference, FG 2009, Bordeaux, France, July 25-26, 2009, Revised Selected Papers - Groote, Philippe; Egg, Markus; Kallmeyer, Laura (LNCS sublibrary. SL 7, Artificial intelligence, 2011)
This book constitutes the refereed proceedings of the 14th International Conference on Formal Grammar 2009, held in Bordeaux, France, in July 2009. The 13 revised full papers presented, including two invited talks, were carefully reviewed and selected from 26 submissions. These articles in this book give an overview of new and original research on formal grammar, mathematical linguistics and the application of formal and mathematical methods to the study of natural language.